Concept and Perspectives for a Pastoral Living Landscape (PLL) on Livestock and Climate Innovations in South Tunisia - Frija, Aymen; Carpentier, Irene; Sghaier, Mongi; Sghaier, Mariem; Rudiger, Udo; Idoudi, Zied; Mannai, Amal (International Center for Agricultural Research in the Dry Areas, 2024)
The technical report presents the Pastoral Living Landscape (PLL) model as a framework designed to promote sustainable pastoral practices, enhance livestock productivity, and build resilience to climate change in Tunisia’s arid southern regions. It explores the benefits of PLLs, including environmental conservation and economic support for pastoral communities, while also addressing the governance challenges in the rangeland and animal feed sectors. Key stakeholders, such as small private entrepreneurs, institutional actors, and farmers’ organizations, play crucial roles in implementing the PLL model, each contributing to innovation and development within the pastoral system. The report further examines local PLL initiatives in regions like Matmata-Tamezret, Gabès, and Medenine, showcasing efforts to organize and empower pastoral communities, improve resource management, and create more inclusive, sustainable livelihoods despite regulatory and structural constraints.